Measuring non‐polyaminated lipocalin‐2 for cardiometabolic risk assessment. (27th June 2017) - Yang, Kangmin; Deng, Han‐Bing; Man, Andy W.C.; Song, Erfei; Zhang, Jialiang; Luo, Cuiting; Cheung, Bernard M.Y.; Yuen, Kwok‐Yung; Jensen, Pia Søndergaard; Irmukhamedov, Akhmadjon; Elie, Atlanta G.I.M.; Vanhoutte, Paul M.; et al.
Abstract: Aims: Lipocalin‐2 is a pro‐inflammatory molecule characterized by a highly diversified pattern of expression and structure–functional relationships. In vivo, this molecule exists as multiple variants due to post‐translational modifications and/or protein–protein interactions. Lipocalin‐2 is modified by polyamination, which enhances the clearance of this protein from the circulation and prevents its excessive accumulation in tissues. On the other hand, animal studies suggest that non‐polyaminated lipocalin‐2 (npLcn2) plays a causal role in the pathogenesis of obesity‐associated medical complications. The present study examined the presence of npLcn2 in samples from healthy volunteers or patients with cardiac abnormalities and evaluated npLcn2 as a biomarker for cardiometabolic risk assessment. Methods and results: Immunoassays were developed to quantify npLcn2 in blood and urine samples collected from 100 volunteers (59 men and 41 women), or venous plasma and pericardial fluid samples obtained from 37 cardiothoracic surgery patients. In healthy volunteers, npLcn2 levels in serum are significantly higher in obese and overweight than in lean subjects. After adjustment for age, gender, smoking, and body mass index (BMI), serum npLcn2 levels are positively correlated with heart rate, circulating triglycerides, high‐sensitivity C‐reactive protein (hsCRP), and creatinine in plasma. The npLcn2 levels in urine are significantly increased in subjects with metabolic syndrome and positively correlated with BMI, heart rate, circulating triglycerides, and urinary aldosterone. In cardiothoracic surgery patients, the circulating concentrations of npLcn2 are higher (more than two‐fold) than those of healthy volunteers and positively correlated with the accumulation of this protein in the pericardial fluid. Heart failure patients exhibit excessive expression and distribution of npLcn2 in mesothelial cells and adipocytes of the parietal pericardium, which are significantly correlated with the elevated plasma levels of npLcn2, total cholesterol, and creatinine. Conclusions: Quantitative and qualitative evaluation of npLcn2 in human biofluid samples and tissue samples can be applied for risk assessment of healthy individuals and disease management of patients with obesity‐related cardiometabolic and renal complications.